2012
DOI: 10.1177/1362361312442790
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of autism spectrum disorder symptomatology and related behavioural characteristics in individuals with Down syndrome

Abstract: We evaluated the proportion of individuals with Down syndrome (DS: N = 108) who met criteria for autism spectrum disorder (ASD) on the Social Communication Questionnaire and the severity of ASD-related symptomatology in this group. The proportions of individuals with DS meeting the cut-off for ASD and autism in this sample were 19% and 8%, respectively. We then evaluated the behavioural profile of individuals with DS who scored above cut-off for ASD (DS+ASD; N = 17) compared with those with DS-only (N = 17) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 43 publications
10
82
3
1
Order By: Relevance
“…5HT2a antagonism could therefore represent a novel therapeutic opportunity in the context of Down syndrome in which frontal functionality is reportedly diminished. For instance, autism spectrum disorders with stereotypy and attention deficits is found in 20-25% of DS children (Ekstein et al, 2011;Ji, Capone, & Kaufmann, 2011;Moss, Richards, Nelson, & Oliver, 2013), and lowering 5HT neurotransmission may improve focused/selective attention (Booij, Van der Does, & Riedel, 2003;Schmitt, Wingen, Ramaekers, Evers, & Riedel, 2006). In a translational research mindset, we show that risperidone, a 5HT2a antagonist used in clinic for improving attention deficits found in autism (Sharma & Shaw, 2012), and also currently being tested in DS (Capone et al, 2008), restored nesting performances in Ts65Dn mice when administered at low doses.…”
Section: Discussionmentioning
confidence: 87%
“…5HT2a antagonism could therefore represent a novel therapeutic opportunity in the context of Down syndrome in which frontal functionality is reportedly diminished. For instance, autism spectrum disorders with stereotypy and attention deficits is found in 20-25% of DS children (Ekstein et al, 2011;Ji, Capone, & Kaufmann, 2011;Moss, Richards, Nelson, & Oliver, 2013), and lowering 5HT neurotransmission may improve focused/selective attention (Booij, Van der Does, & Riedel, 2003;Schmitt, Wingen, Ramaekers, Evers, & Riedel, 2006). In a translational research mindset, we show that risperidone, a 5HT2a antagonist used in clinic for improving attention deficits found in autism (Sharma & Shaw, 2012), and also currently being tested in DS (Capone et al, 2008), restored nesting performances in Ts65Dn mice when administered at low doses.…”
Section: Discussionmentioning
confidence: 87%
“…Although autism spectrum disorder is a heterogeneous group of neurodevelopmental disabilities with different etiologies, it has a significant heritable component (at least 50%). [21][22][23] Given that Down syndrome predisposes to ventriculomegaly, and that ventriculomegaly is associated with autism spectrum disorder, the question of whether rigorous autism assessment should be considered for children with Down syndrome who have had evidence of ventriculomegaly in the postnatal period should be explored in future studies. 19,20 Several recent investigations, using standardized autism-specific assessment tools, report that the frequency of autism spectrum disorder in Down syndrome is more than 15%.…”
Section: Resultsmentioning
confidence: 99%
“…FXS are a suitable group because, similarly to ASD, individuals engage in a wide range of repetitive behaviors and this syndrome is genetically defined in comparison to the ASD cut-off group (Hatton et al 2006;Moss et al 2009;Udwin and Dennis 1995). Finally, DS are a suitable group as there is evidence that individuals with DS engage in fewer repetitive behaviors than those with a codiagnosis of ASD (Hepburn and MacLean 2009;Moss et al 2013b). In particular, Moss et al (2013b) found that individuals with DS and ASD engaged in more stereotyped behavior and repetitive speech than those without ASD.…”
Section: Introductionmentioning
confidence: 98%
“…Finally, DS are a suitable group as there is evidence that individuals with DS engage in fewer repetitive behaviors than those with a codiagnosis of ASD (Hepburn and MacLean 2009;Moss et al 2013b). In particular, Moss et al (2013b) found that individuals with DS and ASD engaged in more stereotyped behavior and repetitive speech than those without ASD.…”
Section: Introductionmentioning
confidence: 98%